2004
DOI: 10.1074/jbc.m400831200
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of the Serotonin Transporter into Lipid Microdomains Modulates Transport of Serotonin

Abstract: The serotonin transporter (SERT) is an integral membrane protein responsible for the clearance of serotonin from the synaptic cleft following the release of the neurotransmitter. SERT plays a prominent role in the regulation of serotoninergic neurotransmission and is a molecular target for multiple antidepressants as well as substances of abuse. Here we show that SERT associates with lipid rafts in both heterologous expression systems and rat brain and that the inclusion of the transporter into lipid microdoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 59 publications
(50 reference statements)
11
148
0
Order By: Relevance
“…Results of real-timebioluminescence recording suggest that SSRI significantly shortened the period in rat-1 fibroblasts and the mouse SCN. SERT is associated with lipid microdomains, which are required for efficient serotonin transport activity (Magnani et al, 2004). Therefore, to further support our findings, SERT activity was blocked using a cholesterol chelating reagent methyl-β-cyclodextrin (β-CD) and lipid binding reagent xylazine.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Results of real-timebioluminescence recording suggest that SSRI significantly shortened the period in rat-1 fibroblasts and the mouse SCN. SERT is associated with lipid microdomains, which are required for efficient serotonin transport activity (Magnani et al, 2004). Therefore, to further support our findings, SERT activity was blocked using a cholesterol chelating reagent methyl-β-cyclodextrin (β-CD) and lipid binding reagent xylazine.…”
Section: Introductionsupporting
confidence: 65%
“…SERT is an N-glycosylated integral membrane protein with 12 transmembrane regions, and has been shown to associate with lipid raft. The association with lipid raft on the cell membrane is required for an efficient 5-HT transporter activity (Magnani et al, 2004). The loss of interaction with lipid microdomains is detrimental to SERT function, possibly due to conformational changes that mainly affect the translocation of the substrate across the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dependence of the uptake activity on the presence of cholesterol has been shown by Magnani et al (38). It may well be that the oligomerization is not directly based on protein-protein interaction but rather on an indirect clustering due to the local lipid environment, as was shown for glycosylphosphatidylinositol-anchored proteins (21,40).…”
Section: Discussionmentioning
confidence: 80%
“…Magnani et al have found that plasma membrane cholesterol is necessary for proper uptake activity of SERT (38). Because the presence of cholesterol has also been found to be important for the oligomerization of various membrane proteins (39,40), we wondered whether cholesterol also has an effect on the distribution of oligomeric states of SERT.…”
Section: C Obtained Brightness Distribution Of the Oligomeric Fractimentioning
confidence: 97%